Impacts of Trichoderma harazanium Extract on snf1, frp1, clc1 Gene Expression in Fusarium oxysporum f.sp lycopersici - AL-Masoudi, Rasha Khalid Hussein; AL Judy, Neamat J. (Iraqi Journal of Science, 2025)
Fusarium oxysporum f. sp. lycopersici is the causal agent of tomato wilt disease. The ability to infect particular plant species depends on specific genes that distinguish virulent fungi from their closely related nonvirulent relatives. These genes encode host-determining "virulence factors," including small, secreted proteins and enzymes involved in the synthesis of toxins. This research aims to study the impact of Trichoderma harazanium extract on the expression of frp1, snf1, and clc1 genes expression on five severely pathogenic isolates of Fusarium oxysporum f.sp. lycopersci for the first time in Iraq. The fungal isolates used in this study were isolated from infected tomato plants in several regions of Iraq. The present results demonstrated the highest inhibition rates of growth for all isolates to be 100% at a 10 mg/ml concentration of T. harazanium extract. In contrast, the minimal inhibitory of 1.25 mg/ml caused inhibition rates of 28.12%, 30.37%, 36.2%, 38.59%, and 43.78%, consecutively. The results of qRT-PCR investigation showed a substantial downregulation of the expression of clc1 gene in all F. oxysporum isolates in contrast to the other genes; the snf1 gene showed a significant downregulation of transcription by 0.4697, 0.2552, and 0.1684 folds in three F. oxysporum isolates (Fox3, Fox 17, and Fox 20, respectively). The frp1 gene showed an insignificant decrease in gene expression in all isolates. These results provide new insights into the molecular pathogenicity of F. oxysporum and demonstrate the possibility of employing these bioagents to influence the virulence genes of fungal phytopathogens.